2014
DOI: 10.1073/pnas.1400247111
|View full text |Cite
|
Sign up to set email alerts
|

Bypass of the pre-60S ribosomal quality control as a pathway to oncogenesis

Abstract: Significance Ribosomopathies are paradoxical: They first appear as diseases caused by too few cells but later present as diseases caused by too many. Here, we show that the presence of too few cells is caused by a quality control system that eliminates mutant ribosomes before they are allowed to translate mRNAs. Genetic suppression of this quality control system increases the amount of ribosomes available to cells. However, this 60S subunit deficiency results in release of defective ribosomes into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 55 publications
1
103
0
Order By: Relevance
“…This may be due to differential effects on pre-rRNA processing when Puf6 is acutely depleted, as we have done here, compared with when the PUF6 gene is deleted, as was done previously. This may be an example of how yeast adapt to chronic defects in ribosome biogenesis (27). These results indicate that the conserved basic residues in mutant group M1a on the inner concave surface of the N-terminal region of Puf6 are important for 7S pre-rRNA processing.…”
Section: Conserved Basic Residues On Puf6mentioning
confidence: 82%
“…This may be due to differential effects on pre-rRNA processing when Puf6 is acutely depleted, as we have done here, compared with when the PUF6 gene is deleted, as was done previously. This may be an example of how yeast adapt to chronic defects in ribosome biogenesis (27). These results indicate that the conserved basic residues in mutant group M1a on the inner concave surface of the N-terminal region of Puf6 are important for 7S pre-rRNA processing.…”
Section: Conserved Basic Residues On Puf6mentioning
confidence: 82%
“…Rpl10l is highly homologous to Rpl10 (61), so we can speculate about Rpl10l functions from various studies of Rpl10, known to be important for nuclear export and allosteric movement of the 60 S ribosomal subunit (62,63). Human RPL10 mutations have been detected in leukemia (64,65) and implicated in abnormal brain development leading to autism (66), intellectual disability (67,68), and microcephaly (69). Moreover, faulty translation resulting from loss of other ribosomal proteins constitutes an important pathogenic mechanism (69,70) and causes diverse developmental defects (71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%
“…The paradoxical observation that ribosome assembly deficits in humans often lead not only to hypoproliferative diseases, such as anemia, but also to hyperproliferative disorders, such as leukemias and cancers, has recently been addressed using a yeast model of the ribosomal protein uL16 R98S mutation that leads to T-cell acute lymphoblastic leukemias (T-ALL) in humans (De Keersmaecker et al 2013;Sulima et al 2014b). It was found that this mutation causes a 60S subunit biogenesis deficit that can be suppressed by mutations in ribosome assembly factors (De Keersmaecker et al 2013;Sulima et al 2014b), leading to the release of functionally compromised subunits into the pool of translating ribosomes (Sulima et al 2014b).…”
Section: The Release Of Eif6 and Its Connection To Ribosomopathiesmentioning
confidence: 99%
“…It was found that this mutation causes a 60S subunit biogenesis deficit that can be suppressed by mutations in ribosome assembly factors (De Keersmaecker et al 2013;Sulima et al 2014b), leading to the release of functionally compromised subunits into the pool of translating ribosomes (Sulima et al 2014b). It has been shown that the absence of a single protein from the eukaryotic ribosome can perturb the expression of specific sets of genes, even if global translation is unchanged (Kondrashov et al 2011).…”
Section: The Release Of Eif6 and Its Connection To Ribosomopathiesmentioning
confidence: 99%
See 1 more Smart Citation